PENGARUH KOMPENSASI KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT TALKINDO SELAKASA ANUGERAHTANGERANG SELATAN(DEPARTEMEN LOGISTIK) - Erik, Erik Rudianto; Lismiatun, Lismiatun (YBAMB, 2024)
ABSTRACT The purpose of this research is to determine the effect of compensation and work motivation on employee performance at PT Talkindo Selaksa Anugerah South Tangerang, both partially and simultaneously. The research method used is a quantitative method with an associative approach. The sampling technique used was saturated sampling technique, namely using a sample of 60 respondents from the entire population. The data analysis techniques used are instrument testing, classical assumption testing, linear regression analysis, correlation coefficient analysis, determination coefficient analysis, hypothesis testing. This is proven by the results of the compensation hypothesis test, which obtained a tcount value of 3,604 > ttable 1,671 and was strengthened by the ρ value < Sig.0.05 or significance value < 0.05 (0.001 < 0.05) and work motivation obtained a tcount value of 5,732 > ttable 1,671 and is strengthened by the ρ value < Sig.0.05 or significance value < 0.05 (0.000 < 0.05). The research results that compensation and work motivation simultaneously have a significant effect on employee performance at PT Talkindo Selaksa Anugerah South Tangerang are shown by the multiple linear regression equation Y = 8.097 + 0.290X1 + 0.527X2. This is proven by the results of simultaneous hypothesis testing obtained by the Fcount value (52,625 > Ftable 3.16) and reinforced by the significance value < 0.00 (0.000 < 0.05). The results of the coefficient of determination test for compensation and work motivation variables have an influence of 80.5% on employee performance at PT Talkindo Selaksa Anugerah South Tangerang. Thus H0 is accepted and H3 is rejected. This means that it is proven that there is no significant influence simultaneously between compensation (X1) and work motivation (X2) on employee performance (Y) Keywords: compensation and work motivation on employee performance